Improved Detection of Bacterial Pathogens in Patients Presenting with Gastroenteritis by Use of the EntericBio Real-Time Gastro Panel I Assay - Koziel, Monika (American Society for Microbiology, 2013)
In this study, we evaluated the use of EntericBio real-time Gastro Panel I (Serosep, Limerick, Ireland) for routine use in a clinical microbiology laboratory for simultaneous detection of Campylobacter jejuni, coli, and lari, Shiga toxin-producing Escherichia coli (STEC), Salmonella spp., and Shigella spp. in feces. This system differs from its predecessor (the EntericBio Panel II system, Serosep) in that it allows real-time detection of pathogens directly from feces, without pre-enrichment. It also specifically detects Campylobacter jejuni, coli, and lari rather than all Campylobacter species, as is the case with the previous system. A total of 528 samples from patients presenting with acute gastroenteritis were screened prospectively with this assay, and results were compared with those of the current method, which combines screening the samples with a molecular assay (the EntericBio Panel II assay) and retrospective culture of the specimens in which the target was detected. Discrepancy analysis was conducted using culture and molecular methods. The real-time assay produced 84 positive results, specifically, Campylobacter spp. (n = 44); Stx1 and/or Stx2 (n = 35); Shigella spp. (n = 3); and Salmonella spp. (n = 6). Of these, 4 samples represented coinfections with Campylobacter spp. and STEC. The real-time assay showed an increased detection rate for pathogens, apart from Salmonella spp. Four Campylobacter-positive and 6 Stx-positive results remained unconfirmed by any other method used. The isolation rates for PCR-positive samples were as follows: Campylobacter spp., 80%; STEC, 45.7%; Salmonella spp., 100%; and Shigella spp., 66.7%. The sensitivity, specificity, positive predictive value, negative predictive value, and efficiency were 100%, 97.8%, 88.1%, 100%, and 98.1%, respectively.